PENYESUAIAN ATAS ANGGARAN DASAR PERSEROAN TERBATAS TERBUKA PASCA DIKELUARKANNYA PERATURAN OTORITAS JASA KEUANGAN No. 32/POJK.04/2014 DAN PERATURAN OTORITAS JASA KEUANGAN No. 33/POJK.04/2014 - FENDY KUSUMA (PREMISE LAW JURNAL, 2017)
By enacting Financial Service Authority Regulation No. 32/POPJK.04/2014 and No. 33/POJK.04/2014, it is certain that there is the amendment in both regulations on Law No. 40/2007; its legal consequence is that a public corporation must adjust its Article of Association both Financial Service Authory regulations. The research used descriptive analytic and judicial normative method. It can be concluded that there are some changes in the both regulation when they are compared with Law No. 40/2007. The changes are made to adjust them to the current needs in order to increase the level of good corporate governance of issuer or public corporation, to maximize the role of board of directors and board of commissioners of issuer or public corporation so that corporation can run positively. The legal consequence od enacting both regulations is that public corporation must readjust it Article of Association within 1 (one) year after both regulations are enacted. Keywords: Financial Service Authority Regulation, Public Corporation, Article of Association